NBCe1-B/C-knockout mice exhibit an impaired respiratory response and an enhanced renal response to metabolic acidosis - Brady, Clayton T.; Marshall, Aniko; Zhang, Chen; Parker, Mark D. (Frontiers in Physiology, 2023)
The sodium-bicarbonate cotransporter (NBCe1) has three primary variants: NBCe1-A, -B and -C. NBCe1-A is expressed in renal proximal tubules in the cortical labyrinth, where it is essential for reclaiming filtered bicarbonate, such that NBCe1-A knockout mice are congenitally acidemic. NBCe1-B and -C variants are expressed in chemosensitive regions of the brainstem, while NBCe1-B is also expressed in renal proximal tubules located in the outer medulla. Although mice lacking NBCe1-B/C (KOb/c) exhibit a normal plasma pH at baseline, the distribution of NBCe1-B/C indicates that these variants could play a role in both the rapid respiratory and slower renal responses to metabolic acidosis (MAc). Therefore, in this study we used an integrative physiologic approach to investigate the response of KOb/c mice to MAc. By means of unanesthetized whole-body plethysmography and blood-gas analysis, we demonstrate that the respiratory response to MAc (increase in minute volume, decrease in pCO2) is impaired in KOb/c mice leading to a greater severity of acidemia after 1 day of MAc. Despite this respiratory impairment, the recovery of plasma pH after 3-days of MAc remained intact in KOb/c mice. Using data gathered from mice housed in metabolic cages we demonstrate a greater elevation of renal ammonium excretion and greater downregulation of the ammonia recycling enzyme glutamine synthetase in KOb/c mice on day 2 of MAc, consistent with greater renal acid-excretion. We conclude that KOb/c mice are ultimately able to defend plasma pH during MAc, but that the integrated response is disturbed such that the burden of work shifts from the respiratory system to the kidneys, delaying the recovery of pH.